Analysis of behavior of sales tax due to implementation of national consumption tax - Corredor-López, Luisa Fernanda (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2014)
This paper focuses on analyzing the taxation behavior in terms of taxpayers, tax collection and economic activities, both in sales tax for the fiscal periods 2012 and 2013, and in the national tax to the consumption during the fiscal period 2013. This analysis centers on knowing the effects of the taxation reform in 2012 regarding these two taxes.